Fine-needle aspiration cytology-induced infarction of thyroid nodule hampers diagnosis - Khushboo Dewan; Poonam Rani; Arti Khatri; Kusum Gupta; Ashish K Mandal (Wolters Kluwer Medknow Publications, 2020)
Fine-needle aspiration cytology (FNAC) is a useful procedure for the investigation of thyroid swellings. It is a safe and minimally invasive procedure but is accompanied by its own set of complications. Infarction of the parent tissue post-FNAC has been reported in the lymph node, salivary gland, and breast but is a rare phenomenon in the thyroid. We present a case of a 34-year-old female with a solitary thyroid nodule. FNAC smears were hypercellular and showed numerous Hurthle cells suggesting a possibility of Hurthle cell neoplasm. Hemithyroidectomy performed 1 month thereafter showed extensive necrosis and hemorrhage with only few atypical follicular epithelial cells and Hurthle cells at the periphery. The near-total infarction and paucity of viable cells made it extremely difficult to make a histopathological diagnosis. The case highlights the need for extensive sampling and thorough examination of the periphery for any viable foci on histopathology along with cytologic-histologic correlation in such cases.